2023
DOI: 10.1038/s41598-023-28291-y
|View full text |Cite
|
Sign up to set email alerts
|

Sign change in c-axis thermal expansion constant and lattice collapse by Ni substitution in transition-metal zirconide superconductor Co1−xNixZr2

Abstract: Recently, c-axis negative thermal expansion (NTE) was observed in a CoZr2 superconductor and related transition-metal zirconides. Here, we investigated the structural, electronic, and superconducting properties of Co1−xNixZr2 to achieve systematic control of c-axis NTE and switching from NTE to positive thermal expansion (PTE) by Ni substitution. At x ≤ 0.3, c-axis NTE was observed, and the thermal expansion constant αc approached zero with increasing x. At x = 0.4–0.6, c-axis thermal expansion close to zero t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…NiZr 2 exhibits PTE both along the a-and c-axes, and thus, the coefficient of volumetric thermal expansion 𝛽 is positive (Figure 1a). [19,20] In the tetragonal crystal structure, 𝛽 can be calculated according to the following equation:…”
Section: Thermal Expansion Under High Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…NiZr 2 exhibits PTE both along the a-and c-axes, and thus, the coefficient of volumetric thermal expansion 𝛽 is positive (Figure 1a). [19,20] In the tetragonal crystal structure, 𝛽 can be calculated according to the following equation:…”
Section: Thermal Expansion Under High Pressurementioning
confidence: 99%
“…[16][17][18] In the TrZr 2 system, we revealed that the uniaxial NTE along the c-axis can be controlled by the lattice constant ratio c/a, through chemical element substitution. [19,20] The sign of the linear coefficient of thermal expansion along the c-axis changes from positive to negative upon the substitution of Ni with Co at ambient pressure. [20] The anomalous bonding states related to the uniaxial NTE along the c-axis in TrZr 2 have also been observed using X-ray absorption spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation